Knowledge, attitude, and practice regarding trauma-informed care among nursing students in Eastern China: A cross-sectional study - Zhang, Di; Songwathana, Praneed; Vachprasit, Ratjai; Holroyd, Eleanor (Belitung Nursing Journal, 2025)
Background: Patients with a history of traumatic life events who enter the healthcare system are especially vulnerable, often posing greater challenges to care delivery. However, little is known about the capacity of nursing staff, especially nursing students, to deliver trauma-informed care (TIC). Objective: This study aimed to assess the knowledge, attitude, and practice of trauma-informed care among Chinese nursing students. Methods: A cross-sectional study was employed to survey undergraduate nursing students from a medical college in eastern China. Data were collected using an established self-administered questionnaire on TIC knowledge, attitude, and practice (KAP) consisting of 21 items. The content validity scale-level CVI was 0.950, and the reliability with Cronbach’s α coefficient was 0.963. Results: A total of 118 undergraduate nursing students, ranging from first to fourth year, participated in the survey, and ultimately, 117 students were included in the study, yielding an effective response rate of 99.15%. The average scores for KAP were 70.83±14.58, 77.78±11.11, and 66.67±16.67; however, the good levels of KAP accounted for 16.2%, 45.3% and 6.0%, respectively. Additional analysis showed a weak positive correlation between knowledge and attitude (rs = 0.211, p = 0.022), while there was a moderate positive correlation between knowledge and practice, attitude and practice (rs = 0.309, p < 0.001; rs = 0.310, p < 0.001). Univariate analysis indicated that year of study and experience in caring for trauma patients were significantly related to practice (p = 0.039, p = 0.002). Conclusion: The students’ KAP on trauma-informed care was not at a good level, especially regarding practice and knowledge, and required further strengthening. The findings provide baseline information for further development of a KAP-TIC comprehensive course and exploration of practice ability-centered TIC education for nursing students. Assessing the effectiveness of the newly developed TIC course and learning outcomes in clinical practice is also recommended.